Mathematical modelling of motorcycle sale competition in Indonesia - Windarto, ,- (CMBN, 2021)
Motorbike is a means of transportation that is widely used in Indonesia and other developing countries. In this paper, we apply the Lotka-Volterra competition mathematical model to describe the dynamics of motorcycle sale competition between two motorcycle producers in Indonesia. We also estimate the parameter values of the model using the particle swarm optimization method. We found that the mathematical model quite well to explain the annual motorcycle sales of both companies. The results of the model analysis show that the competition between the two motorcycle producers is pure competition, with the first producer dominates market share of motorcycle selling in Indonesia.